Forward Osmosis in India: Status and Comparison with Other Desalination Technologies. (29th October 2014) - Mehta, Dhruv; Gupta, Lovleen; Dhingra, Rijul
Abstract : With an increase in demand of freshwater and depleting water sources, it is imperative to switch to seawater as a regular source of water supply. However, due to the high total dissolved solid content, it has to be desalinated to make it drinkable. While desalination technologies have been used for many years, mass deployment of such technologies poses a number of challenges like high energy requirements as well as high negative environmental impact through side products and CO2 emissions. The purpose of this paper is to present a sustainable technology for desalination. Forward osmosis, an emerging technology, is compared with the other commonly used technologies worldwide, namely, multieffect distillation, multistage flash distillation, and reverse osmosis as well as other emerging technologies like vapour compression, solar humidification dehumidification, nanofiltration, and freezing desalination. As energy consumption and associated greenhouse gas emissions are one of the major concerns of desalination, this paper concludes that forward osmosis is an emerging sustainable technology for seawater desalination. This paper then presents the challenges involved in the application of forward osmosis in India and presents a plant setup. In the end, the cost comparison of a forward osmosis and reverse osmosis plant has been done and it was concluded that forward osmosis is economically better as well.